Electrochemical study of ephedrine at the polarized liquid-liquid interface supported with a 3D printed cell - Poltorak, Lukasz; Rudnicki, Konrad; Kolivoška, Viliam; Sebechlebská, Táňa; Krzyczmonik, Paweł; Skrzypek, Sławomira (Journal of hazardous materials, 2021)
In this work, we have examined an electrochemical behavior of the ephedrine at the polarized liquid-liquid interface (water/1,2-dichloroethane). In this respect, we first designed and then 3D printed polyamide-based electrochemical cell that was used as the liquid-liquid interface support during electroanalytical measurements. The protonated ephedrine undergoes a reversible ion transfer reaction with the standard Galvani potential difference equal to +0.269 V. This value was used to calculate the water - 1,2-dichloroethane logP equal to -4.6. Ion transfer voltammetry was used to build the calibration curve and allowed for the ephedrine detection from concentration equal to 20 μM. By varying the pH of the aqueous phase from 2 up to 12 we were able to plot the ion partition diagram that was further analyzed and provided several pharmacochemical information. To further push this work towards practical utility, we have formulated the artificial urine and studied the interfacial behavior of all its components at the polarized liquid-liquid interface. Ephedrine detection from real spiked urine samples was also performed.
Keywords: voda; Ethylene Dichlorides; ion transfer voltammetry; illicit drugs; methamphetamine precursor; 3D tisk; Printing, Three-Dimensional; ITIES; Ephedrine; 3D printing; Water; efedrin; sensing; ethylendichloridy